Training on Using Google Data Studio for Real-Time and Interactive Management of Beji Village Data and Information - Rachmad Andri Atmoko; Salnan Ratih Asriningtias; Myro Boyke Persijn (Jurnal Pengabdian Masyarakat Bestari, 2022)
The use of information technology is very important to support speed and ease in serving the community. However, at the village level there is still a shortage of specialized staff in the field of providing information technology-based applications. So, it is necessary to do community service in the form of technical guidance to take advantage of the use of applications such as Google workspace. Google workspace makes it very easy to manage data and information management. The data collection process is carried out using the Google form, data processing uses Google sheets, and administrative work can use the collaboration feature on Google Docs. This community service program is intended to explore Google workspace facilities, in creating data visualization dashboards using Google Data Studio. Villagers can monitor the movement of data in real-time against input from the Google form in the form of interactive graphics so that it can be used as a basis for making decisions more quickly.